Tecnologia educacional aplicada à educação permanente para profissionais de saúde: Uma análise do Núcleo de Telemedicina e Telessaúde Goiás (2017-2022) - Camila Costa da Silveira; Leandro do Prado Assunção; Alexandre Chater Taleb; Flavio Marques Lopes (Revista Contexto & Saúde, 2026)
Introduction/Objective: This study aims to analyze the tele-education initiatives developed by the Goiás Telemedicine and Telehealth Center (NUTTs) through online classes held between 2017 and 2022, focusing on the topics covered, the duration of the activities, and the alignment of the content with the needs of primary care professionals. Method: The methodology employed a descriptive, exploratory, and qualitative-quantitative approach. Data from 2017 to 2022 were analyzed in collaboration with NUTTs. The data analysis was structured in three stages: (1) descriptive analysis, calculating the absolute frequency of topics, broken down by year; (2) calculation of the total and average duration of the web-based classes, also broken down by year; and (3) analysis of the keywords associated with the topics of each web-based class. Results: The results revealed a total of 620 web-based classes covering various fields from 2017 to 2022. The fields with the highest number of web-based classes over the years were psychology (181 web-based classes offered), nutrition (121 web-based classes offered), and nursing (83 web-based classes offered). The shortest web-based classes were in medicine, biomedicine, and social work, while those in physical therapy, nursing, and dentistry were the longest. The topics most frequently covered in the web-based classes were yellow fever, general diseases, nutrition, COVID-19, childhood obesity, cancer, and nutrition for cancer patients. Conclusion: This study highlights the fundamental role of information and communication technology in the continuing education process for healthcare professionals.